Clinical and molecular characterization of hepatic glycogen storage disease in Saudi Arabia - Abdulrahman Al-Hussaini; Mohammed AlMannai; Muhannad Alruwaithi; Eissa Faqeih; Ali Alasmari; Majid Alfadhel; Fuad Al Mutairi; Mohammed Saleh; Abdullah AlZaben; Yaser Alobailan; Moodhi Alharbi; Manal AlAfqi; et al. (PLoS ONE, 2025)
Background and objectives The paucity of data on glycogen storage diseases (GSDs) from Arabs prompted us to report on hepatic GSD to characterize its clinical and molecular features and outcomes among Saudi children and to evaluate genotype‒phenotype correlations. Methods We retrospectively reviewed the charts of 65 children (37 females) with genetically confirmed hepatic GSD who presented between 2008 and 2020 and were followed up for a median duration of 9 years (range: 0.4–21 years). Results The most common hepatic GSD in our cohort was GSD Ia (37%), followed by GSD III (20%), GSD Ib (12.3%), and GSDVI (10.8%). Twenty-seven variants were identified (8 novel and 4 from the common ancestor, i.e., “founder in nature”). The most common founder variant is P.(Arg83Cys) in the G6PC1 gene (20% of the 65 GSD patients), clustering in Aseer Province. Six patients underwent liver transplantation (due to difficulty controlling hypoglycemia in 5 GSD Ia patients and severe portal hypertension in one GSD IV patient). One patient with GSD type 1b developed hepatic adenoma at the age of 17 years. A patient with GSD IXc developed portal hypertension at the age of 5 years, and one patient with GSD IXa developed cirrhosis. Renal complications developed in 18 patients. An echocardiogram was performed in 16 patients and revealed mild–moderate asymptomatic left ventricular hypertrophy in 5 patients. The majority of the hepatic GSD cases in our cohort manifested a severe phenotype (hepatomegaly, hypoglycemia, ± systemic involvement); only the 7 GSD VI patients manifested a mild phenotype (hepatomegaly without hypoglycemia). No “genotype‒phenotype correlations” could be observed when the two common G6PC1 gene variants [p.(Arg83Cys) versus p.(Gln20Arg)] were compared. Conclusion With the exception of GSD VI, all the hepatic GSD subtypes in Saudi Arabia are associated with a severe phenotype. Identification of the predominant gene variants and their geographic distribution in any population is likely to facilitate rapid molecular analysis by future targeting of that specific mutation.